Antioxidant and ACE-Inhibitory Activity of Protein Hydrolysates Produced from Atlantic Sea Cucumber (Cucumaria frondosa) - Tharindu R. L. Senadheera; Abul Hossain; Deepika Dave; Fereidoon Shahidi (Molecules, 2023)
Atlantic sea cucumber is a benthic marine echinoderm found in Northwest Atlantic waters and is harvested mainly for its body wall. The body wall, along with internal organs and aquaphyrangeal bulb/flower, is a rich source of proteins, where the latter parts are often considered as processing discards. The objective of this research was to produce protein hydrolysates from sea cucumber tissues (body wall, flower, and internal organs) with bioactive properties associated with antioxidants, DNA and LDL cholesterol oxidation inhibition, and angiotensin-I-converting enzyme (ACE) inhibitory effects. The protein hydrolysates were prepared using food-grade commercial enzymes, namely Alcalase, Corolase, and Flavourzyme, individually and in combination, and found that the combination of enzymes exhibited stronger antioxidant potential than the individual enzymes, as well as their untreated counterparts. Similar trends were also observed for the DNA and LDL cholesterol oxidation inhibition and ACE-inhibitory properties of sea cucumber protein hydrolysates, mainly those that were prepared from the flower. Thus, the findings of this study revealed potential applications of sea cucumber-derived protein hydrolysates in functional foods, nutraceuticals, and dietary supplements, as well as natural therapeutics.